2021
DOI: 10.1530/ec-21-0360
|View full text |Cite
|
Sign up to set email alerts
|

Obese patients with higher TSH levels had an obvious metabolic improvement after bariatric surgery

Abstract: Objective: Bariatric surgery has become the most effective treatment for morbid obesity. Increasing evidence showed that bariatric surgery can alleviate insulin resistance and influence thyroid function. This study aimed to investigate the relationship between changes in thyroid function and adipose tissue insulin resistance (adipo-IR) after bariatric surgery. Methods: A total of 287 non-diabetic participants with regular thyroid function were recruited and divided into the lean, overweight and obese groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The FFA, total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and serum creatinine (Scr) were measured by colorimetric enzymatic assays using a biochemical auto-analyzer (Hitachi 7170). FBG, FINS, and glycated hemoglobin (HbA1c) levels were detected as previously described (28). The estimated glomerular filtration rate (eGFR) was calculated as previously described (29).…”
Section: Anthropometric and Biochemical Measurementsmentioning
confidence: 99%
“…The FFA, total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and serum creatinine (Scr) were measured by colorimetric enzymatic assays using a biochemical auto-analyzer (Hitachi 7170). FBG, FINS, and glycated hemoglobin (HbA1c) levels were detected as previously described (28). The estimated glomerular filtration rate (eGFR) was calculated as previously described (29).…”
Section: Anthropometric and Biochemical Measurementsmentioning
confidence: 99%
“…Overweight euthyroid patients also showed a correlation between elevated TSH levels and fat accumulation, with TSH levels positively associated with weight gain (18)(19)(20). Various studies have shown that bariatric surgery in obese patients improves their thyroid profile (41)(42)(43). A meta-analysis revealed that bariatric surgery has a positive impact on subclinical hypothyroidism, reducing TSH levels and lowering the required dose of thyroid hormone replacement therapy in patients with severe obesity (44).…”
Section: Discussionmentioning
confidence: 99%
“…The negative values indicated higher sensitivity to FT4 in the pituitary, positive values indicated less sensitivity, and the value of 0 indicated a normal sensitivity. In thyroidal and peripheral tissues, FT4 is converted to the active free triiodothyronine (FT3) hormone through a process that can be assessed using the FT3:FT4 ratio ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%